Microinvasive squamous cell carcinoma of uterine cervix with superficial spread to endometrium: a rare case report - Arora, Ritu; Bhagat, Nisha; Raj, Rajnish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Microinvasive squamous cell carcinoma of uterine cervix is defined as carcinoma with invasion of less than 5 mm penetration of the stroma. The spread to uterine corpus occurs rarely, but on lateral spread it involves parametrium and deep myometrium via lymphatic dissemination. Less than 30 cases are reported in literature of superficial spread of microinvasive carcinoma of cervix. We report a case of microinvasive squamous cell carcinoma of cervix with metastasis to uterine corpus due to superficial spread.